2019
DOI: 10.1128/jvi.01297-18
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection of Cell Lines Derived from Diffuse Large B-Cell Lymphomas Alters MicroRNA Loading of the Ago2 Complex

Abstract: Diffuse large B-cell lymphoma (DLBCL) is an aggressive lymphoid tumor which is occasionally Epstein-Barr virus (EBV) positive and is further subtyped as activated B-cell DLBCL (ABC-DLBCL) and germinal center B-cell DLBCL (GCB-DLBCL), which has implications for prognosis and treatment. We performed Ago2 RNA immunoprecipitation followed by high-throughput RNA sequencing (Ago2-RIP-seq) to capture functionally active microRNAs (miRNAs) in EBV-negative ABC-DLBCL and GCB-DLBCL cell lines and their EBV-infected count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Regarding miRNAs upregulated following EBOV infection ( Table 1 and Table 2 ), it is interesting to note the existence of strain-specific miRNAs that can be detected during the early stage of infection and that may serve as precocious biomarkers, and potentially contribute either positively or negatively to the virulence and pathogenicity of the EBOV strains. For example, Mayinga seemed to correlate in a specific manner with miR-363-3p (belonging to miR-106-363 cluster), a regulator of apoptosis and proliferation in various cell lines, including those derived from the liver [ 97 , 98 , 99 ]. The Makona strain was associated with miR-132-3p which is known to promote H1N1 Influenza A Virus replication by suppressing type I interferon response through targeting Interferon Regulatory Factor 1 (IRF1) [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding miRNAs upregulated following EBOV infection ( Table 1 and Table 2 ), it is interesting to note the existence of strain-specific miRNAs that can be detected during the early stage of infection and that may serve as precocious biomarkers, and potentially contribute either positively or negatively to the virulence and pathogenicity of the EBOV strains. For example, Mayinga seemed to correlate in a specific manner with miR-363-3p (belonging to miR-106-363 cluster), a regulator of apoptosis and proliferation in various cell lines, including those derived from the liver [ 97 , 98 , 99 ]. The Makona strain was associated with miR-132-3p which is known to promote H1N1 Influenza A Virus replication by suppressing type I interferon response through targeting Interferon Regulatory Factor 1 (IRF1) [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of miR-21, miR-155 and miR-221 has been found to be upregulated in the non-GCB subtype compared to the GCB subtype of cancer (25). Additionally, upregulation of miR-221-3p and downregulation of let-7c-5p in the non-GCB type, and upregulation of miR-363-3p and downregulation of 423-5p in patients with GC-DLBCL, has recently been reported (26). Yang et al also demonstrated a role for miR-197 as a biomarker with potential therapeutic implications (27).…”
Section: Discussionmentioning
confidence: 94%
“…Ago2-IP was performed as described previously [92]. Briefly, two 15 cm plates of AGS-BGLF2 cells or AGS-EBV-Z cells with WT or BGLF2 knockout virus at ~50 confluency were treated with 2 μg/ml Dox for 48 hours (or left untreated).…”
Section: Ago2 Immunoprecipitationmentioning
confidence: 99%